Evaluation of height-diameter models for community Parkia biglobosa Jacq B. plantation in wasangare, Oyo State. (2023)
Forest growth and yield models are fundamental tools for sustainable forest management planning and future inventory assessments. In order to quantify the growing stock of Parkia biglobosa in Wasangare, Oyo state, reliable height-diameter (H-D) models are required. Therefore, the aim of this study was to evaluate 2-parameter H-D models for the prediction of heights of Parkia biglobosa tree which are consistent with current forest management practices in the country. Measured 1,196 pairs of height and diameter data were subjected to six (6) 2-parameter H-D models viz Naslund, Meyer, Curtis, Modified Log Logistic, Michaelis-Menten and Wykoff. Model fitting and validation was done in ratio 75:25. With the use of R software tools, the fitting and validation was done. Root mean square error (RMSE), mean absolute bias (MAB), Akaike information (AIC) and Bayesian information criterion (BIC) were used to assess the models. The result showed that all the models were significant but based on the goodness-of-fit statistics, Meyer H-D model had the least rank value, followed by the Modified log logistics H-D (M. LogL) model. The Meyer H-D model had RMSE, MAB, AIC and BIC of 2.996, 2.389, 4520.263 and 4524.660 respectively while M. LogL HD model had 2.999, 2.421, 4522.082 and 4536.480 respectively. Therefore, it was concluded that Meyer H-D model and M. LogL model written as and, respectively were selected as the best candidate models for H-D relationships of Parkia biglobosa plantation especially in the savanna zone of Oyo state.